Analisis Bauran Komunikasi Pada Layanan Pembiayaan di KSPPS Karisma Grabag dalam Meningkatkan Minat Nasabah - sofian, Alif; Fitriyani, Yeny; Pudail, M (ITB AAS INDONESIA Surakarta, 2023)
This study aims to find out more and describe the state of the marketing communication mix implemented by the KSPPS Karisma branch of Grabag to arouse the interest of members and increase the number of their members. Increasing The failure of cooperatives to attract members is one of the factors. There is a lack of marketing communications while members are the source. Cooperative survival requires good marketing communications, informing the existence of products and convincing people to make purchases. The method used is descriptive qualitative method in this study. The data analysis method used is data collection, presentation of the data found and conclusions. Information obtained from observations and interviews where the sampling technique was purposive sampling, documentation, internet and literature research was carried out from January 2022 to December 2022. The marketing communication mix used by KSPPS Karisma Grabag to reach members is advertising, personal selling, and word of mouth marketing, direct and interactive marketing and public relations and Advertising. The marketing communication mix used in this study Kharisma KSPPS Grabag increased the number of members.